A Versatile and Robust Vesicle Based on a Photocleavable Surfactant for Two‐Photon‐Tuned Release. Issue 24 (15th April 2013) - Dong, Jianming; Xun, Zhiqing; Zeng, Yi; Yu, Tianjun; Han, Yongbin; Chen, Jinping; Li, Ying‐Ying; Yang, Guoqiang; Li, Yi
Abstract A small amphiphile that contains a coumarin unit and alkynyl groups, as a two‐photon‐cleavable segment and polymerizable groups, respectively, was designed and synthesized. The amphiphile showed a critical aggregation concentration of about 4.6×10−5 M and formed a vesicle‐type assembly. The formed vesicles were stabilized by in situ "click" polymerization without altering their morphology. Hydrophobic and hydrophilic guests can be encapsulated within the vesicle membrane and inside the aqueous core of the vesicle, respectively. The loaded guests can be released from the vesicle by using UV or near‐IR stimuli, through splitting up the amphiphilic structure of the amphiphile. Distinguished dose‐controlled photorelease of the polymeric vesicle is achieved with the maintenance of vesicular integrity, which makes the guest release dependent on the amount of cleavage of the amphiphilic structure during irradiation. This study provides a potential strategy for the development of versatile and stable drug‐delivery systems that offer sustained and photo‐triggered release.